Investing in Private Equity in Brazil - Antônio Marcos Duarte Junior (FUCAPE Business School, 2016)
ABSTRACT We consider the problem of selecting private equity funds for investment in Brazil. The proposed methodology is based on multi-criteria decision-making. Real data obtained from one of the largest pension funds in Brazil is used to illustrate a practical application of the methodology when selecting investments among eleven private equity funds available in the local financial market. The multi-criteria method TOPSIS is adopted with a total of twenty two criteria to order the investment alternatives. A sensitivity analysis is also presented. The methodology proposed allows a standardized decision-making process, facilitating the process of selecting private equity funds for investment in Brazilian financial markets.